Formulation of fortified instant weaning food from Musa paradisiaca (banana) and Eleusine coracana - Kabeer, Safreena; Govindarajan, Nagamaniammai; Radhakrishnan, Preetha; Alharbi, Hanan F.; Essa, Musthafa Mohamed; Qoronfleh, M. Walid (Frontiers in Nutrition, 2023)
Abstract: Weaning food is a soft, easily digestible food other than breast milk for consumption of infants aged 6 to 24 months. The present study was carried out to develop cereal-fruit based complementary food for infants and to evaluate the nutritional quality of such product. Few researchers have focused their ability to formulate weaning food from locally available nutritious rich ingredients without nutrients loss in order to reduce malnutrition and infants morbidity rate. In this study, the formulated infant food was prepared from Musa paradisiaca (Nendran banana) and Eleusine coracana (Ragi). Formulated weaning food was analyzed using various standard methods demonstrating that it could furnish an adequate amount of nutrients to growing infants for their proper growth and development. The shelf-life of the weaning food was also studied for a period of three months at ambient condition in two different packaging materials Aluminum and Plastic (low density polyethylene-LDPE) with aluminum foil pouch exhibiting the best shelf-life. This ready–to–serve formulated, fortified weaning food could be considered as an effective supplementary food for infants that is made of natural ingredients and possess the required macro- and micronutrients. Potentially, this development may bring forth an affordable weaning product for low socioeconomic groups.